Pedagogical leadership: an experience of collaboration and professional learning in a school in the context of the COVID-19 pandemic - Hidalgo, Óscar (2023)
The global pandemic due to COVID-19 brought various challenges for schools that have had to continue to ensure the educational process of children and young people. In this context, the study seeks to describe teachers' subjectivity regarding the organization's redesign to respond to the need for distance learning. The experience was developed in a school in the Araucania Region in Chile with 81 teachers from the Basic and Secondary Education levels. The collection of information was carried out through interviews and focus groups as dialogue instances with the teachers that helped to raise awareness about the process developed. The results show the relevance of pedagogical leadership that provides the organizational and professional conditions conducive to improving teaching practices and the students' learning processes. Exercising this kind of leadership reconfigured management, valuing collaborative work between teachers as a process in which pedagogical practice is learned and transformed. Although the school continues to promote changes and improvements, it is concluded that the situation caused by the pandemic represents an opportunity to move towards the training of a professional learning community that is constantly searching for practices that promote deep learning for students.